MAKNA DIBENARKAN OLEH IMAN MENURUT GALATIA 3:1-14 - Sinuraya, Samuel Julianta (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
Since humans fell into sin, the relationship between God and humans has been damaged. Christ's death became peace between God and humans. Paul in Galatians 3:1-14 wrote that humans are justified by faith in Christ. This research is qualitative research with a grammatical historical approach. The aim of this research is to find the meaning of being justified by faith according to Galatians 3:1-14. For Paul, humans are justified by faith in Christ's death which is found in experience and contemplation or reflection in the Bible.